Dietary protection against the visual and motor deficits induced by experimental autoimmune encephalomyelitis - Zyla-Jackson, Katarzyna; Walton, Dorothy A.; Plafker, Kendra S.; Kovats, Susan; Georgescu, Constantin; Brush, Richard S.; Tytanic, Madison; Agbaga, Martin-Paul; Plafker, Scott M. (Frontiers in Neurology, 2023)
Five to eight percent of the world population currently suffers from at least one autoimmune disorder. Despite multiple immune modulatory therapies for autoimmune demyelinating diseases of the central nervous system, these treatments can be limiting for subsets of patients due to adverse effects and expense. To circumvent these barriers, we investigated a nutritional intervention in mice undergoing experimental autoimmune encephalomyelitis (EAE). This model of autoimmune-mediated demyelination induces visual and motor pathologies similar to those experienced by people with multiple sclerosis (MS). Here, we report that limiting dietary carbohydrates by feeding mice a ketogenic diet (KD) enriched in medium chain triglycerides, -linolenic acid, and fiber is effective at mitigating EAE-induced optic neuritis and motor deficits. The KD was efficacious when fed as a preventive regimen prior to EAE immunization as well as when initiated as an interventional regimen following the onset of EAE symptoms. The KD minimally impacted body weight during the experimental time course, increased circulating ketones, prevented motor and ocular deficits, preserved myelination of the optic nerve, and reduced infiltration of immune cells to optic nerves. The KD also increased anti-inflammatory-associated omega-3 fatty acids in the plasma and reduced select cytokines in the circulation associated with EAE-mediated pathological inflammation. In light of ongoing clinical trials using dietary strategies to treat people with MS, these findings support that a KD promotes a systemic anti-inflammatory milieu and ameliorates autoimmune-induced demyelinating visual and motor deficits.